Antibacterial Potential of Kecombrang (Etlingera elatior) Leaf Extract as a Natural Ingredient in Facial Cleansing Soap - Sri Purwati; Jailani Jailani; Muhammad Ridho; Volta Kelik Setiawan; Rimbawan Apriadi (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2026)
Kecombrang (Etlingera elatior) leaves are known to contain bioactive compounds such as tannins, flavonoids, and saponins with antibacterial properties. This study aimed to evaluate the antibacterial potential of kecombrang leaf extract and its application in facial cleansing soap formulation against Staphylococcus aureus. The extract was prepared by ethanol maceration, phytochemical screening was conducted, and antibacterial activity was tested using the well diffusion method. The extract showed the highest antibacterial activity at a 40% concentration, producing an inhibition zone of 10.4 ± 0.34 mm. Furthermore, the extract was incorporated into liquid soap formulations with varying potassium hydroxide (KOH) amounts (50–84 g) and reaction times (35–65 min). The optimized formula with 67 g KOH and 65 min reaction time exhibited the largest inhibition zone of 13.28 ± 0.41 mm, while the formula with 50 g KOH and 35 min reaction time showed the lowest free fatty acid (FFA) level (1.541%), making it safer for daily use. These findings indicate that kecombrang leaf extract has promising potential as a natural antibacterial ingredient in environmentally friendly facial cleansing soap.